Про роботу Південної середньовічної експедиції у 2009 р. - Біляєва, С.О.; Карашевич, І.В.; Фіалко, О.Є. (Археологічні дослідження в Україні, 2010)
Results are presented of a 2009 study of mediaeval monuments of the north coast of the Black Sea. Excavations and a set of nondestructive archaeological works were conducted in Bilhorod-Dnistrovskyi of Odesa Oblast and Ochakiv of Mykolayiv Oblast.